2017
DOI: 10.2147/jmdh.s118419
|View full text |Cite
|
Sign up to set email alerts
|

Role of the multidisciplinary team in the care of the tracheostomy patient

Abstract: Tracheostomies are used to provide artificial airways for increasingly complex patients for a variety of indications. Patients and their families are dependent on knowledgeable multidisciplinary staff, including medical, nursing, respiratory physiotherapy and speech and language therapy staff, dieticians and psychologists, from a wide range of specialty backgrounds. There is increasing evidence that coordinated tracheostomy multidisciplinary teams can influence the safety and quality of care for patients and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 70 publications
1
49
0
8
Order By: Relevance
“…[1][2][3][4] One must rapidly recognize and appropriately intervene when airway-related complications occur to provide safe care and prevent harm. 2,7,8 Regardless of the etiology of an acute decompensation event in the tracheostomy-dependent child, primary management consists of establishing a patent airway by suctioning and/or replacing the tracheostomy tube. 8 Many centers, including ours, have patients with tracheostomy and ventilator requirements on the pediatric wards where residents provide care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] One must rapidly recognize and appropriately intervene when airway-related complications occur to provide safe care and prevent harm. 2,7,8 Regardless of the etiology of an acute decompensation event in the tracheostomy-dependent child, primary management consists of establishing a patent airway by suctioning and/or replacing the tracheostomy tube. 8 Many centers, including ours, have patients with tracheostomy and ventilator requirements on the pediatric wards where residents provide care.…”
Section: Introductionmentioning
confidence: 99%
“…7,11 Therefore, resident physicians tasked with caring for patients with tracheostomy and ventilator requirements require specialized training to safely and confidently perform the appropriate steps for tracheostomy tube suctioning and replacement. 7,[11][12][13] Simulations have long been shown to provide a safe space for learners to practice unfamiliar skills. 14 Simulation has been used in the tracheostomy patient population to create realistic clinical scenarios that allow learners to seek feedback, reflect, and learn with no risk to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…These complications demands a multidisciplinary team approach, with good coordination between its team members, for evaluation and rehabilitation to ensure the safety and quality care of these patients. 10,11 In a study, Mah et al concluded that, "the introduction of care bundle for post tracheostomy care to the multidisciplinary tracheostomy service significantly improve oral diet intake as well as decannulation". 12 Thus restoration of function of respiration, phonation, feeding and swallowing demands a strict integration and participation among different members of the multidisciplinary rehabilitation team.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing inpatient tracheostomy‐related complications requires institution‐wide protocols for tracheostomy care, implementing simple preventative and rescue measures, and ensuring that staff trained in rescue measures are available at the bedside within minutes of an emergency to intervene before permanent hypoxic injury occurs. Coordinated multidisciplinary teams and protocol‐driven, institution‐wide efforts involving all providers involved in tracheostomy care drastically reduces tracheostomy‐related catastrophic events and mortality. Institutional tracheostomy care improvement efforts in the United Kingdom and Australia reduced tracheostomy‐related adverse events by over 90%, with similar success replicated in the United States .…”
Section: Discussionmentioning
confidence: 99%